Austerity and collective bargaining in Spain: The political and dysfunctional nature of neoliberal deregulation. (September 2016) - Rodríguez, Carlos J Fernández; Rojo, Rafael Ibáñez; Lucio, Miguel Martínez
This article focuses on changes in collective bargaining in Spain during the current phase of austerity. We evaluate how the decentralization and transformation of collective bargaining have affected industrial relations and forms of work and suggest that the policy reforms have led to a deterioration in working conditions and a weakening in collective regulation and trade unions. However, we emphasize the contradictory outcomes, which appear to be drawing the state into new more direct roles, bringing new actors (such as legal firms) into the deregulation of employment. This situation also raises a range of concerns among managers and employers at the repoliticization of industrial relations and generates further challenges to the ability of management and unions to sustain consensual forms of social dialogue.